Perceptions of junior doctors and undergraduate medical students as anatomy teachers: Investigating distance along the near‐peer teaching spectrum. Issue 3 (29th October 2013) - Hall, Samuel; Stephens, Jonathan; Andrade, Teu; Davids, Joseph; Powell, Matthew; Border, Scott
<x xml:space="preserve">Abstract</x> Near‐peer teaching involves more experienced students acting as tutors and has been widely used in anatomy education. This approach has many advantages for the learner due to the social and cognitive congruence they share with the teacher, however, the influence of distance between the teacher and learner on these congruences has yet to be explored. The aim of this study was to compare the attitudes and perceptions of the student learner towards neuroanatomy review sessions taught by either a senior medical student or a junior doctor. The students were randomly assigned to an allocated tutor. All tutors used standardized material and had access to identical resources. The type of allocated tutor was swapped between the two teaching sessions and 99 student feedback forms were collected in total. The rating for the overall quality of the teaching session was not significantly different between the junior doctors and senior medical students (P = 0.11). However, criteria closely relating to social and cognitive congruence such as "enjoyment of the session, " "delivery of the teaching, " and "was it a good use of time" were all rated significantly higher for the senior medical students (P < 0.05). The results of this study suggest that small increases in distance along the near‐peer teaching spectrum have an impact upon the student's perception of their learning experience. While all teachers were suitable role models it appears that junior doctors are too far removed from their own undergraduate experiences to share congruences with pre‐clinical medical students. Anat Sci Educ 7: 242–247. © 2013 American Association of Anatomists.